Evaluation of the Tribological and Corrosion Resistance Properties of 24-Bilayer TiN/TiAlN Coatings in Simulated Body Fluid - Willian Arnulfo Aperador Chaparro; Julio Cesar Caicedo Angulo; Jorge Bautista-Ruiz (Tribology in Industry)
The tribocorrosive behavior of [TiN/TiAlN] coatings, consisting of 24 bilayers with a bilayer period (Λ) of 125 nm, was evaluated. There is a lack of studies on the tribocorrosion of TiN/TiAlN multilayer coatings applied to metallic prostheses. These coatings were obtained using a reactive RF magnetron sputtering system and deposited onto a Ti6Al4V alloy. This study represents the first evaluation of the tribocorrosive behavior of these coatings in simulated physiological environments. Various characterization techniques were employed, including X-ray diffraction (XRD), scanning electron microscopy (SEM), atomic force microscopy (AFM), pin-on-disk testing, electrochemical impedance spectroscopy (EIS), and Tafel curves. The coatings exhibited a face-centered cubic (FCC) structure, characterized by a partial arrangement of Ti and Al atoms. The research is motivated by the need for tribocorrosion-resistant coatings to enhance the durability of metallic prostheses. The results demonstrated a friction coefficient of 0.053 and a corrosion rate of 0.025 µm/year, highlighting the effectiveness of the coating. Changes in roughness were observed; however, no significant alterations in its formation were noted.